2009
DOI: 10.1016/j.cub.2009.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Location-Specific Cortical Activation Changes during Sleep after Training for Perceptual Learning

Abstract: SUMMARY Visual perceptual learning is defined as performance enhancement on a sensory task and is distinguished from other types of learning and memory in that it is highly specific for location of the trained stimulus. The location specificity has been shown to be paralleled by changes in neural activity in V1 or V4 of monkeys [1, 2] and enhancement in functional magnetic resonance imaging (fMRI) signal in the trained region of the primary visual cortex (V1) [3–5] after visual training. Although recently the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
123
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 30 publications
11
123
1
Order By: Relevance
“…Reactivation of the hippocampus was observed during sleep following a spatial navigation task [67], whereas visual texture discrimination led to reactivation in those parts of V1 that are specifically involved in learning the task [23]. Importantly, the level of reactivation predicted subsequent performance improvement in both of these tasks.…”
Section: Offline Memory Replaymentioning
confidence: 95%
See 1 more Smart Citation
“…Reactivation of the hippocampus was observed during sleep following a spatial navigation task [67], whereas visual texture discrimination led to reactivation in those parts of V1 that are specifically involved in learning the task [23]. Importantly, the level of reactivation predicted subsequent performance improvement in both of these tasks.…”
Section: Offline Memory Replaymentioning
confidence: 95%
“…This mechanism is compelling in its simplicity and in its effortless fit to the literature on reactivation of memories in rats [21,22] and humans [23][24][25][26], as well as to research on concept formation [27]. It explains why newly learned material becomes increasingly easy to integrate and remember as a conceptual schema takes shape [18,19].…”
mentioning
confidence: 99%
“…Strengthening of cortical memory traces is also thought to involve "replay," a term that refers to the reinstantiation of neural activity elicited by a prior experience. Replay is coordinated by lowfrequency oscillatory activity (Jensen, 2006;Sirota et al, 2008), and has been shown in both hippocampal-based memory formation (Wilson and McNaughton, 1994;Hoffman and McNaughton, 2002) and skill-related memory formation (Stickgold et al, 2000;Yotsumoto et al, 2009). Another important systems-level factor is the requirement to segregate different memory traces.…”
Section: Discussionmentioning
confidence: 99%
“…Training-induced response changes have been shown after prolonged training (Schoups et al, 2001) but also after a single training session (Schwartz et al, 2002;Yotsumoto et al, 2008). Moreover, human neuroimaging (Yotsumoto et al, 2009) has revealed offline V1 activity during sleep 6 h after a single session of visual skill learning, implicating V1 in offline consolidation after a small amount of training. In contrast, influential theories of visual skill learning (Karni and Bertini, 1997;Ahissar and Hochstein, 2004) predict that the contribution of low-level visual areas to offline consolidation is maximized toward the end of learning (late, asymptotic phase) rather than at the beginning (early phase).…”
Section: Introductionmentioning
confidence: 99%